Transformation of Research Systems in Central and Eastern Europe: Lessons for Ukraine - Yegorov, I.Yu. (Science and Innovation, 2024)
The milestones and characteristics of research system transformation in Central and Eastern Europe have been discussed. Major problems of the development and the EU role in the corresponding processes of transformation have been determined; the barriers on the path towards the reforms and the factors which contribute to positive transformations have been identified. Recommendations on reforming the research sphere in Ukraine have been proposed.